Prospective Evaluation of RedTouch Laser in the Treatment of Dry Eye Disease Secondary to Meibomian Gland Dysfunction - Vergés C; Ribas V; Salgado-Borges J; Giménez-Capitán A; March de Ribot F (Clinical Ophthalmology, 2025)
Carlos Vergés,1 Veronica Ribas,1 José Salgado-Borges,1,2 Ana Giménez-Capitán,3 Francesc March de Ribot1,4 1Department of Ophthalmology, Dexeus University Hospital, University of Barcelona, Barcelona, Spain; 2Clinsborges, Porto, Portugal; 3Pangaea, Laboratory of Oncology, Dexeus University Hospital, Barcelona, Spain; 4Department of Ophthalmology, Girona Hospital, Girona University, Catalunya, SpainCorrespondence: Carlos Vergés, Dexeus University Hospital, Sabino Arana, 19, Barcelona, 08028, Spain, Tel +34 667570322, Email cverges@cverges.comPurpose: To validate the efficacy of RedTouch laser, a new 675 nm laser system in treating dry eye disease (DED) secondary to Meibomian gland dysfunction (MGD), comparing generalized periocular treatment versus direct targeting of the meibomian glands.Patients and Methods: 70 patients with mild and moderate DED-MGD received 4 sessions of laser treatment separated by 3 weeks, with assessments before treatment, T0, and at the end, T1, after 2 months from the last session. Patients were divided randomly into 2 groups (G1 and G2) of 35 patients each to test different protocols. In G1, the eyelids and periocular area were treated with a 675 nm laser and G2, with the same treatment as in G1 but combined with a free pencil-shaped handpiece on the tarsal conjunctiva of the superior and inferior eyelids as well as on the lid margin of both eyelids.Results: The outcomes resulted in a significant improvement in all symptoms and signs of both groups, OSDI, CFS, NITMH, NITBUT, Osmolarity and Schirmer test1. However, G2—receiving additional targeted meibomian gland treatment—showed superior outcomes across all parameters (G1 vs G2, p < 0.001), including the signs of the Meibomian glands and the lid margin (G1 vs G2, p < 0.001).Conclusion: RedTouch laser is an effective treatment in patients with DED related to MGD, improving signs and symptoms. While periocular skin treatment alone provides clinical benefits, outcomes are significantly better when the laser is applied directly to the lid margin and tarsal conjunctiva, targeting the meibomian glands more specifically. No complications were observed.Keywords: dry eye disease, meibomian gland dysfunction, 675 nm laser, ocular surface